2020
DOI: 10.14202/vetworld.2020.1588-1593
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of antimicrobial resistance and virulence genes of Escherichia coli isolates from bovine mastitis

Abstract: Background and Aim: Mastitis is a common and economically important disease in dairy cattle. It remains one of the most common reasons for the extensive use of antimicrobials in dairy farms leading to the emergence of antimicrobial-resistant pathogens. The aim of this study was to determine the patterns of antimicrobial resistance of Escherichia coli isolates from bovine mastitis and to identify prominent antimicrobial resistance and virulence genes among isolated strains. Materials and Methods: Antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
4
14
0
Order By: Relevance
“…There are many studies in the field of animal products that have suggested that the repeated use of antibiotics has increased the prevalence of different bacterial strains that carry many highly pathogenic genes against the many antibiotics used to treat these bacteria ( Srinivasan et al, 2007 ). Consequently, truthful identification, careful usage of antibiotics, and the application of an effective antimicrobial drug to treat the various contagious illnesses should be applied to restrict the development and distribution of multidrug-resistant microorganisms among animals and humans ( Ismail and Abutarbush, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many studies in the field of animal products that have suggested that the repeated use of antibiotics has increased the prevalence of different bacterial strains that carry many highly pathogenic genes against the many antibiotics used to treat these bacteria ( Srinivasan et al, 2007 ). Consequently, truthful identification, careful usage of antibiotics, and the application of an effective antimicrobial drug to treat the various contagious illnesses should be applied to restrict the development and distribution of multidrug-resistant microorganisms among animals and humans ( Ismail and Abutarbush, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of multi-drug resistant E. coli strains recovered from mastitic milk and clinical samples is considered a public health alarm worldwide ( Kahlmeter and Poulsen, 2012 , Copur-Cicek et al, 2014 ). Previous scientific reports have proven that there is a close correlation between the amazing development of multidrug-resistant E. coli strains from different animals and those from human clinical samples ( Rasheed et al, 2014 , Walther et al, 2017 , Ismail and Abutarbush, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Farshad et al (2012), the presence of this microorganism in raw milk and dairy products is serious, as it can cause diseases such as uremic hemolytic syndrome, hemorrhagic colitis, and bloody diarrhea; this is why we seek to reduce bacterial contamination of milk to the greatest extent possible. In a recent study with cattle, 14 isolates from milk were identified as E. coli (Ismail & Abutarbush, 2020), a zoonotic bacterium that needs to be under constant surveillance.…”
Section: Discussionmentioning
confidence: 99%